Leveraging Automation and Traceability in Managing Changes to Mission-Critical Computer Systems - Zangana, Hewa; Ali, Natheer Yaseen; Bazeed, Sameer Mohammed Salih; Abdullah, Dilovan Taha (Indonesian Journal of Education and Social Sciences, 2025)
Managing changes to mission-critical computer systems presents unique challenges, especially when reliability, security, and real-time performance are paramount. Traditional change management processes can be inefficient and error-prone, leading to potential disruptions. This study employs case studies from the finance, healthcare, and defense sectors to illustrate the real-world impact of automation and traceability in managing mission-critical system changes. Through empirical evidence, this paper demonstrates that automation and traceability significantly enhance change management by reducing human errors by 30%, improving audit efficiency, and accelerating approval workflows. Through leveraging advanced automated tools and establishing traceability mechanisms, organizations can minimize human error, ensure compliance with regulatory standards, and streamline approval workflows. Case studies from various industries highlight the successful application of these techniques, demonstrating their role in maintaining operational continuity, enhancing system integrity, and reducing downtime. The findings underscore the transformative impact of automation and traceability in safeguarding mission-critical systems against risks associated with frequent or complex changes. Empirical analysis from case studies indicates that automation reduces change-related downtime by 35% and enhances compliance tracking by 40%, demonstrating its effectiveness in maintaining operational resilience. Unlike previous studies that primarily focus on change management frameworks in general IT projects, this research specifically examines the intersection of automation, traceability, and cybersecurity in mission-critical systems. By providing empirical evidence from real-world case studies, it offers a structured approach to integrating these elements, contributing to both theoretical discussions and practical implementations in high-stakes industries.